Analisis Hukum Pelaksanaan Olah Tempat Kejadian Perkara dalam Penegakan Hukum Pidana Melalui Pencarian Alat Bukti - Erick Darmansyah; Gunardi Lie (CV Rewang Rencang, 2024)
Murder is a grave crime that threatens human life and social order, necessitating meticulous investigation to achieve material truth as mandated by the Indonesian Code of Criminal Procedure. Governed by Articles 1(14), 6, and 7 of Indonesian Code of Criminal Procedure and Law No. 2 of 2002 on the Indonesian National Police, investigations authorize investigators to receive reports, examine witnesses, secure crime scenes, and collect evidence. Determining the tempus delicti (time of the crime) is critical for reconstructing events, validating evidence, and identifying perpetrators, yet it is hindered by limited forensic technology, inconsistent witness statements, and weak inter-agency coordination. Crime scene processing, utilizing forensic analysis such as linkage theory and post-mortem examinations, is pivotal in establishing the time of the crime, as stipulated in Article 184(1) of Indonesian Code of Criminal Procedure. However, Indonesia’s lack of forensic laboratories, inadequate investigator training, and inconsistent standard operating procedures often lead to evidence contamination or failed prosecutions, potentially resulting in acquittals. Ethical violations by rogue investigators, such as abuse of authority, further erode legal legitimacy and public trust. This study employs a normative juridical approach, analyzing legislation, legal principles, and doctrines related to murder investigations to evaluate the effectiveness of crime scene processing, structural challenges, and compliance with positive law, including Indonesian Code of Criminal Procedure and the 1945 Constitution. The study recommends forensic reforms, enhanced investigator integrity, and improved inter-agency coordination to support substantive justice in a rule-of-law state.